Design of Storage Allocation Using Interaction Frequency Heuristic-Order Oriented Slotting Approach to Reduce Delay Time on Traveling Searching Activities in Refinery Unit V Warehouse PT XYZ - Putra, Ardi Kelana; Ridwan, Ari Yanuar; Aurachman, Rio (Jurnal Rekayasa Sistem Industri, 2018)
Â Refinery Unit (RU) V is a processing company owned by PT XYZ located in Balikpapan. Refinery Unit V has twelve warehouses with four warehouses being the main focus in this research of RGM, RMS, RIN, and RSP used to store products for refinery maintenance processes. In the initial conditions, there is a delay in traveling searching activities. The occurrence of delay in traveling searching activity caused by the absence of details of the product location clearly. The proposed product allocation is using Interaction Frequency Heuristic-Order Oriented Slotting method. The last step is to create a new layout for each RU V warehouse.The first step is to calculate the cycle time for each work order list by calculating the distance between the storage point with the point of I / O based on the aisle distance calculation. Next is to compare between the cycle time of each work order list with the standard time of the warehouse, so it will know the percentage of work order list that experienced delay for one year. Next, allocate product storage based on the popularity value of the product and the value of the interaction frequency between the products. The final step is to simulate using new work order list based on the proposed allocation layout to know the effect of change from the proposed layout. The result of this research is a new layout for each warehouse. All stock taking performance are better than the standard time while the exisiting condition violate the standard time.